IMPLEMENTASI BILANGAN BULAT PADA PERMAINAN TRADISIONAL CONGKLAK - Hilmi Zaki Islahati; Rezza Trie Kusdayati; Saluky Saluky (Jurusan Matematika, IAIN Syekh Nurjati Cirebon, 2021)
Many traditional games apply mathematics, Congklak is a game that contains elements of mathematics, one of which is integer operations. This paper applies the material to integers with a sub-discussion of the mixed arithmetic operation method of integers. While the purpose of this study is to determine the implementation of number theory on the subject of integers, namely the operation of counting integers in the Congklak game. In this paper, the game is carried out as usual but has been modified in order to implement the learning objectives. The results of the study show that students indirectly learn integers and are easy to understand.